Behaviour of pinned beam-to-column connections for precast concrete frames [compact disc] - 447385 Chan, Dennis Paul Leong (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2006